A DIVERSITY OF HELMINTH PARASITE INFECTION OF THE FISHES OF JATINGA RIVER, ASSAM INDIA - SINGH, NGASEPAMI ROMIEN; SHOMORENDRA, M.; KAR, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
Fishes are one of the important elements in the economy of many nations as well as they have been a stable item in the diet of many people, Parasites (in the larval stage) consumed in uncooked or undercooked seafood can present a human health hazard. Fish disease due to helminth parasites is one of the important problems in fish culture and fish farming. The importance of the fish parasites is related directly to the importance of the fish they may affect. There is a bewildering array of fish parasites and probably all the fish species harbour one or more parasite species. A total of 988 different fishes were sacrifices during my investigation, 20 different fish species were examined for helminth parasites infection. Of these 417 fish individual belonging to 14 different fish species are found to be parasitized with a total of 283 helminth parasites. River Jatinga contribute 49 fish species under 32 genera, 17 family and 6 orders. About 14 different species of parasite groups (viz. Nematode-NT, Acanthocephalan-AC and Cestodes-CT) including two new species were recorded from Jatinga River (Table 3). The prevalence and intensity is highest in Mastacebelus armatus and Mystus canvasius respectively (59.09%, 7.2) and lowest in Tenualosa ilisha, Channa punctata and Sperata alor respectively (3.13%, 0.5,0.5) of River Jatinga.